CFD MODELLING OF COOLING CHANNEL GEOMETRY OF PEM FUEL CELL FOR ENHANCED THERMAL PERFORMANCE (Nigerian Journal of Technology, 2017)
Proton exchange membrane (PEM) fuel cell has many distinctive features that make it an attractive alternative clean energy source, including low start-up, high power density, high efficiency, portability and remote applications. An approach to stem the thermal build-up within the fuel cell structure that could lead to degradation of the system components is by integrating cooling channels as part of flow structure of the PEM fuel cell system. In this study, a numerical investigation was carried out to determine the impact of cooling channel geometry in combination with temperature dependent operating parameters on thermal management and overall performance of a PEM fuel cell system. The evaluation is performed using a computational fluid dynamics (CFD) code based on a finite volume approach. The systems performances are presented as a function of the system temperature, operating parameters and cooling channel geometry. The results obtained indicate that incorporating cooling channels within the fuel cell structures improves the PEM fuel cell system performance at higher temperature of operation and optimal aspect ratio of the cooling channels exist for maximised fuel cell performance for the fuel cell model considered. In addition, the parameters studied were optimized using a mathematical optimization code integrated with the CFD code. http://dx.doi.org/10.4314/njt.v37i1.20